Impact of Aerosol on Atmospheric Ozone over Langtang National Park, Nepal - Shrestha, Prakash M.; Gupta, Suresh P.; Rai, Krishna B.; Joshi, Usha; Chapagain, Narayan P.; Karki, Indra B.; Poudyal, Khem N. (Journal of Indigenous Knowledge and Practice, 2025)
This paper reports the impact of aerosols on atmospheric ozone over Langtang National Park. The daily ground-based data of AOD and TOC are received from the Aerosol Robotic Network of NASA for a period of one-year 2018. The daily, monthly and seasonal variations of AOD and TOC are analyzed. The annual average of AOD for visible light are found 0.039 ± 0.037, 0.056 ± 0.049 and 0.064 ± 0.056 respectively. For infrared, the annual average of AOD are found 0.027 ± 0.026 and 0.031 ± 0.030 respectively. For ultraviolet, annual average of AOD are found 0.074 ± 0.064 and 0.079 ± 0.069 respectively. During the study period, the annual average of TOC is found 265 ± 2 DU. There is positive impact of AOD on TOC with moderate correlation coefficient. The result of this work is beneficial for the further analysis of AOD, TOC and their impact at different places.